Rancang Bangun Sistem Kontrol Panel Surya Dua Dimensi Berbasis Arduino - Johny Custer; M Idham M Idham; Jefri Lianda (UIN Sultan Syarif Kasim Riau, 2016)
The position of the solar panel permanently attached will not produce the maximumoutput power. The method used to maximize the power output from the solar panel to adjust theposition of the solar panels are always dealing with the position of the sun. This paper describesthe design of the control system of solar panel with two dimensional base arduino. The solarpanels are driven by two motors. Motor axis X to move towards the east to the west by thechange of time in hours and Y axis motors for movement towards the south to the north basedon the time change by month. The results of this study were able to control the solar panel toget the maximum power of 491 watts. Rated voltage generated by the solar panels can bedisplayed on the LCD via the voltage sensor.Keywords: Arduino, motor, power, solar panel